2012
DOI: 10.1007/s12263-012-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on nutrient intake

Abstract: The relationship between genetic and the environment represents a pathway to better understand individual variations in nutrition intake and food preferences. However, the present literature is weakened somewhat by methodological flaws (e.g., overreliance on self-report questionnaires), discrepancies in statistical approaches, and inconsistent findings. Little research on this topic to date has included examination of micronutrient intake. The purpose of this study is to improve the existing literature on gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Within this context, a recent report highlighted the lack of studies examining genetic contribution to micronutrient intakes [90]. The present study contributes to this field in a number of ways: not only by examining micronutrient intake, overall food intake and dietary patterns in relation to the TAS2R38 genotype, but also by examining BMI z-scores, a known indicator for weight-related disease.…”
Section: Discussionmentioning
confidence: 87%
“…Within this context, a recent report highlighted the lack of studies examining genetic contribution to micronutrient intakes [90]. The present study contributes to this field in a number of ways: not only by examining micronutrient intake, overall food intake and dietary patterns in relation to the TAS2R38 genotype, but also by examining BMI z-scores, a known indicator for weight-related disease.…”
Section: Discussionmentioning
confidence: 87%
“…Understanding the relative contribution of genes and the environment to food selection remains a major challenge in the fields of nutrigenetics and nutrigenomics (e.g., Reed ; Liu et al. ). There is convincing support from studies on humans and rodent models that macronutrient intake has a genetic basis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in general agreement with sexual selection theory, which predicts that female fitness will be maximized through a "low wear and tear" strategy that yields moderate rates of return over longer time periods (Graves 2007;Bonduriansky et al 2008), and is consistent with the fact that female T. commodus, on average, live longer than males under both natural (Zajitschek et al 2009a) and seminatural (Zajitschek et al 2009b) conditions. Understanding the relative contribution of genes and the environment to food selection remains a major challenge in the fields of nutrigenetics and nutrigenomics (e.g., Reed 2008;Liu et al 2013). There is convincing support from studies on humans and rodent models that macronutrient intake has a genetic basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic effects could account for much of the heterogeneity among the population in terms of nutrient intake and personal food preferences. For example in a population-based, twin design study, it was recently confirmed that genetic influences and non-shared environment account for a significant portion of the total energy and macronutrient intake—almost half of the variance in total energy, macronutrients and minerals [ 2 ]. The implications of interaction between genetics and environmental factors on nutrition can be further expanded to a variety of physical and mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%